Answer:
The proof is given below.
Step-by-step explanation:
Given:
The identity to verify is given as:
[tex]\frac{\cos (x-y)}{\sin (x+y)}=\frac{1+\cot x.\cot y}{\cot x+\ cot y}[/tex]
Consider the left hand side of the identity.
[tex]\because \cos (A-B)=\cos A\cdot \cos B+\sin A\cdot \sin B\\ \sin (A+B)=\sin A\cdot \cos B+\sin B\cdot \cos A[/tex]
[tex]= \frac{\cos (x-y)}{\sin (x+y)}\\=\frac{\cos x\cdot \cos y+\sin x\cdot \sin y}{\sin x\cdot \cos y+\sin y\cdot \cos x}\\[/tex]
Dividing both numerator and denominator by [tex]\sin x\cdot \sin y[/tex]. This gives,
[tex]=\frac{\frac{\cos x\cdot \cos y}{\sin x\cdot \sin y}+\frac{\sin x\cdot \sin y}{\sin x\cdot \sin y}}{\frac{\sin x\cdot \cos y}{\sin x\cdot \sin y}+\frac{\sin y\cdot \cos x}{\sin x\cdot \sin y}} \\\\\\=\frac{\cot x\cdot \cot y+1}{\cot x+\cot y}\\\\=\frac{1+\cot x.\cot y}{\cot x+\ cot y}=RHS[/tex]
We have used the identity [tex]\cot A = \frac{\cos A}{\sin A}[/tex] above.
Therefore,
[tex]\frac{\cos (x-y)}{\sin (x+y)}=\frac{1+\cot x.\cot y}{\cot x+\ cot y}[/tex]
Therefore, LHS = RHS and hence proved.